1971
DOI: 10.1302/0301-620x.53b4.609
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Wide Laminectomy for Lumbar Disc Excision

Abstract: 1. The results of wide laminectomy of the fifth lumbar vertebra and disc excision in 132 patients are reviewed and compared with some published results of the interlaminar operation. 2. There was no significant difference in either the immediate or the long-term results of the two operations suggesting that post-operative morbidity was not related to operative technique. 3. The incidence of post-operative back pain was found to increase with age at operation, duration of pre-operative symptoms and length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
2

Year Published

1973
1973
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 11 publications
1
36
0
2
Order By: Relevance
“…Some patients have recurrent herniations after disc excision. There are many studies on such recurrences in which reoperation rate is reported to be 3.8-24% [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several conditions were involved in these reoperation rates: recurrence at the same disc level and same side as the primary herniation [2,4,9,10,13,14], contralateral herniation at the same disc level [4,6,10,11,13,14], or new herniation at a different spinal level [1,4,9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients have recurrent herniations after disc excision. There are many studies on such recurrences in which reoperation rate is reported to be 3.8-24% [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several conditions were involved in these reoperation rates: recurrence at the same disc level and same side as the primary herniation [2,4,9,10,13,14], contralateral herniation at the same disc level [4,6,10,11,13,14], or new herniation at a different spinal level [1,4,9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32]71 Ultimately, these effects can lead to paraspinal muscle atrophy, scarring, and decreased extensor strength and endurance, and can contribute to increased postoperative and long-term pain. 24,35,46,48,52,60,61,69,79 In an effort to mitigate the morbidities associated with conventional open spine procedures, recent advances in minimal access technologies have led to the application of minimally invasive approaches to all regions of the spine for decompression, arthrodesis, and instrumentation. Until recently, the vast majority of advancements in minimally invasive thoracic spine surgery have been based on the thoracoscope.…”
mentioning
confidence: 99%
“…We do not accept this, and no case has been encountered in this series; this was evident by the maintenance of clinical improvement in all cases and absence of further slip in repeated check Xrays in the three spondylolisthetic patients. There are many recent reports (Jackson 1971 In conclusion, it may be stated that the cauda equina syndrome is a relatively common manifestation in lumbar disc herniation' and is usually caused by associated structural changes in the spine. T h e results of wide laminectomy are gratifying.…”
Section: Discussionmentioning
confidence: 98%